TOTOR SORANGAN DALAM UPACARA PENABALAN RAJA SISINGAMANGARAJA SEBAGAI MEDIA PEMBELAJARAN TRANSFORMATIF - Iskandar Muda; Irwansyah Irwansyah; Martozet Martozet (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The highlight tortor is a dance performed at King Sisingamangaraja's dedication program. This study examines the light tortor with the meaning of community life systems that believe in supernatural forces, and serve as strategies and methods in developing transfomative learning development models. Design development is done by identifying the elements of learning material through the development of interactive audio visual media, to see the transformation, both in terms of form, function and meaning, changing from sacred to profane form, but in the context of the performance cannot ignore the ritual requirements. Data collection methods use observation, interviews, documentation, and data validity. Based on the research results of the Sorangan Tortor Transformation by raising the king's ordination ceremony into the form of performance art. Sorangan tortor occurrence factors are influenced by internal and external factors. The highlight tortor is currently undergoing a transformation from the seventh ceremonial form to the performing arts. Keywords: Transformation, Tortor, King Sisingamangaraja's Inheritance